TINJAUAN EKONOMI SYARIAH ATAS PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK BRAND LOKAL DI KOTA PALANGKA RAYA - Akbar, Wahyu; Tarantang, Jefry; Mirnawati, Elda (Pusat Riset dan Inovasi Nasional, 2021)
The focus of this research is to find out whether there is an effect of product quality and price on consumer purchasing decisions on local fashion products in Palangka Raya City. Product quality and price are factors that can influence consumer purchasing decisions and are often used by consumers as a basis for consideration of a product until they decide to make a purchase. This research uses a quantitative approach method. This type of research uses field data on WYD (Wear Your Design) distribution of Palangka Raya as a local brand maker of Palangka Raya. Methods of data collection using questionnaires. The sampling technique used was accidental sampling. The population in this study used the Lemeshow formula and obtained a sample of 96 respondents. The data analysis technique used is multiple linear regression analysis technique. The results showed that based on the results of the partial test statistical calculations, it was concluded that product quality and price had a partial and simultaneous effect on people's purchasing decisions at WYD Distro Palangka Raya. The implementation of Islamic economic values ​​in the form of the value of benefit and justice in production and consumption activities in this study.